FAZLUR RAHMAN: PEMIKIRAN HADITS DAN SUNNAH - Atika Zuhrotus Sufiyana (VICRATINA, 2019)
Fazlur Rahman uses a new method in understanding the hadiths and sunnahs of the prophet Muhammad SAW, namely the hermeneutic approach. The use of this hermeneutic approach is not to agree with the hermeneutic truth that was born from the West but to introduce that through this method Islam is able to match its existence. The focus of the study in this paper discusses Fazlur Rahman's opinion about Hadith and Sunnah and their implications for the appearance of Islamic law. The results of this study: 1) sunnah is a concept of protection, sunnah does not necessarily have absolute specific content, sunnah does not have to contain authentic text which is exactly the same as the Prophet. Sunnah may be born from the interpretation and adjustment of the shohabah or afterward according to the circumstances surrounding it. 2) The hermeneutic approach used by Fazlur Rahman will generate new and dynamic thoughts in accordance with the problems of the modern world that we are living in. Hadith as the second source after the Qurán will be able to face the problems of modernity without having to leave the source of the teachings of the Prophet Muhammad. Thus, the hadith will no longer occupy an awkward position but it will become a living, developing and dynamic tradition.